A comparative study of episiotomy suturing using suture material chromic catgut versus Rapide Vicryl and its outcome - Ruge, Trupti; A., Lathasri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Episiotomy is a surgical incision which is made in the perineum to enlarge the vaginal opening for birth, with a purpose to facilitate the completion of the second stage of labour to improve both the maternal and the neonatal outcomes. A significant number of women experience perineal trauma following vaginal deliveries which may result in perineal pain, dyspareunia and faulty healing. The type of suture material which is used, will influence these factors. Objectives were to assess the effect of suture materials (Rapide Vicryl versus catgut) used in episiotomy and evaluate the wound healing characteristics on day 2 and day 7. Methods: All the pregnant women in labour admitted in labour room of Navodaya medical college, 200 patients satisfying the inclusion and exclusion criteria were taken and were assigned in one of the groups for episiotomy and suturing was done using either of the materials-Vicryl Rapide 2-0 or chromic catgut 1-0, followed up the women in the postnatal ward on day 2 and day 7 and look for immediate complications of episiotomy like temperature, severe pain, hematoma induration, wound gapping and discharge. Results: Among a total of 200 cases, at 48 hours, there was no significant difference according to the pain measurement scores, but the median consumption of analgesics was significantly lower with fast-absorbing polyglactin 910. There was no difference in the association with dysparenia at 6 weeks after the delivery between chromic catgut (19%) compared with standard polyglactin 910 group (8%). Conclusions: Fast-absorbing form of polyglactin sutures are preferred over chromic catgut because of their non- allergic properties, increased tensile strength, lesser probability of pain and lower chances of infection.